Short-Term Perception of Recovery after Surgical Removal of Impacted Third Molar - Jain, Dr. Sanyam; Gokkulakrishnan, Dr. S.; Kumar Diwakar, Dr. Jitendra (International Journal Of Drug Research And Dental Science, 2025)
Background: The surgical removal of third molars, or wisdom teeth, is a common oral and maxillofacial procedure that often presents postoperative challenges such as pain, swelling, and restricted jaw function. While clinical recovery parameters are well-documented, patient-perceived recovery progress remains variable and influenced by multiple factors. Objective: This study aims to assess the subjective experiences of patients undergoing third molar extraction, focusing on perceived pain levels, postoperative swelling, functional recovery, and complications during the first postoperative week. Methods: A three-month observational study was conducted at the Department of Oral and Maxillofacial Surgery, Institute of Dental Sciences, BIU, Bareilly. The study included 45 healthy adult patients (aged 18-35 years) who underwent surgical third molar extraction. Data collection involved patient-reported outcomes assessed at 24 hours, 72 hours, and 7 days postoperatively. Parameters included pain levels (measured using the Visual Analogue Scale), difficulty in mouth opening, swelling, and complications. A structured questionnaire was used to evaluate the impact of surgery on daily activities, social interactions, and overall quality of life. Results: The majority of patients reported significant postoperative discomfort, with peak pain occurring within the first 24 hours (VAS score of 6). Swelling was most pronounced on the second postoperative day before gradually subsiding. Functional limitations, such as restricted mouth opening and chewing difficulties, were most evident during the first three days but improved over the study period. A small proportion of patients reported delayed healing and temporary difficulty in mouth opening as complications. Despite these challenges, most patients rated their overall recovery experience as positive, with effective pain management contributing to satisfactory outcomes. Conclusion: Third molar extraction significantly affects patients’ quality of life during the early postoperative phase, with pain, swelling, and functional impairment being primary concerns. However, patient education, effective analgesic use, and proper postoperative care can enhance recovery experiences. The findings highlight the need for individualized patient management strategies to improve overall satisfaction and optimize postoperative recovery.